Romantic irony as aesthetic skepticism. On Hegel’s critique of the idea of “transcendent poetry” - Vieweg, Klaus (Estudios de Filosofía, 2002)
To understand Hegel’s debate against the concept of Romantic irony proposed by Friedrich Schlegel, it is imperative to detail the si rong relation between Negativity, Skepsis and irony. New light can be shed upon the liaisons between the Philosophy of irony and the Philosophy of the Absolute ift he closeness and distance of the inner Skeptic st rategies developed by Schlegel and Hegel are considered. For the latter, Schlegel’s irony is a manifestation of an absolute, infinite Negativity: a character of aesthetic Skepsis. For Schlegel himself, it is the "supreme and purest Skepsis". By no means can the Skepticism be incorporated amidst the constant fluctuations of "self-creation and self-destruction ", amidst the eternal switching between discourse and counter discourse, thought and counter-thought. The attempt to reunify poetry and philosophy by means ofa “transcendental poetry-" has the same Achilles heel as the Ancient Pyrrhonism -oscillating between narration and discourse, trapped between them, it starves like Buridan donkey. Those ironists stay in the pure Negativity and their endless and longing deed resembles a fruitless conversation. For Hegel, the program of the early Romanticism moves between two extremes: yawning tedium and vital, critic and skeptic creativity.